Dietary (Poly)phenols in Traumatic Brain Injury - Carecho, Rafael (2023)
Funding Information: This research was funded by the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation program under grant agreement No 804229. iNOVA4Health Research Unit (LISBOA-01-0145-FEDER-007344), which is co-funded by Fundação para a Ciência e Tecnologia (FCT)/Ministério da Ciência e do Ensino Superior, through national funds, and by FEDER under the PT2020 Partnership Agreement, is acknowledged (UIDB/04462/2020 and UIDP/04462/2020) as well LS4FUTURE Associated Laboratory (LA/P/0087/2020). The authors would like to acknowledge FCT for financial support: RC (PD/BD/135492/2018) DC (2020.04630.BD); IF (2022.00151.CEECIND). Publisher Copyright: © 2023 by the authors.